Addressing a person by their first name and patronymic as a convention of politeness - Berdiyeva , Zulfiya (The Lingua Spectrum, 2025)
This article examines addressing individuals by their first and last name as a convention of politeness. Addressing someone by their first and last name is particularly used when interacting with strangers, high-ranking officials, or older individuals. The article explores the cultural significance of this convention, the situations in which it is used, and the importance of adhering to it. In conclusion, addressing a person by their first and last name as a convention of politeness plays a significant role in personal and professional relationships and contributes to creating a positive atmosphere in society.